Profile of the person who will undergo bowel elimination ostomy in the preoperative phase - Silva, Carla (2016)
Introduction: Colorectal cancer is a major cause for the confection of an ostomy intestinal elimination (Krouse et al, 2016.). In Portugal it is estimated that about 20 to 25 thousand people are living with an ostomy disposal (Cabral, 2009). It is therefore important to know the profile of this population group in the stage prior to surgery because of its influence on the period after the confection of ostomy and the process of rehabilitation and adaptation of the person to the new condition. Objective: To describe the sociodemographic and clinical characteristics and treatment of the person that will be submitted to ostomy intestinal elimination in northern Portugal. Methods: quantitative, descriptive and cross. It was applied in the form “Development of the person’s self-care competence with intestinal elimination ostomy - CAO-EI”, validated for the Portuguese population, a convenience sample of 50 participants in three northern hospitals in the country. Results: The mean age of participants was 61 years, ranging in ages between 25 and 85 years. It was found that 88% had education, although these, about 71% had attended the 1st cycle. Also 60% were male, 86% were married or living in union and 78% had a family caregiver, and in 62% of cases the spouse. All participants were waiting for colorectal surgery with possible construction of bowel elimination of ostomy and everyone knew refer the diagnosis that motivated the surgery, and 78% had rectal carcinoma, 82% would undergo colostomy and 52% temporary ostomy. Most participants (82%) had never contacted someone with stoma, 58% participated in Stomatherapy Nursing consultation and half of the sample was made marking the stoma. Conclusions: Knowledge about the profile sociodemographic, clinical and treatment of people who will undergo ostomy intestinal elimination, even in the preoperative phase, allows nurses to identify in advance the most vulnerable developing a less adjusted adaptation process, allowing them to mobilize and coordinate resources to and prescribe nursing interventions that respond to the specific needs of this group population.